COLONIALISM IN JOSEPH CONRAD’S HEART OF DARKNESS - NUR LAILATUR ROFI'AH (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
A study was done on a literature work, novel by Joseph Conrad’s Heart of Darkness . this study is done because this novel does not contain a story that entertain but also inform the adequate data about the historical aspect to its reader. The phenomenon that informed is colonialism and its influence toward the changing character of the story. The objective of the study is to describe the colonialism that written in the Heart of Darkness and and its influence toward the changing character of Mr. Kurtz. This study used the qualitative description as research methodology which involved with library research, internet browsing, historical text that related to the research study. The result of this study shown that the colonialism in the novel was a mission of civilization toward the savage that had been distorted in to a force, exploitation violence to the native. And the colonialism spirit and its circumtances can influence person inside become savage too. The conclusion of this study is that civilization can not be the reason of colonialism, whereas the violence and exploitation are only done by savage.